2017
DOI: 10.1177/1077558717697015
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Support for Family Caregivers: Impact on Veteran Health Care Utilization and Costs

Abstract: This study aimed to examine the early impact of the Program of Comprehensive Assistance for Family Caregivers (PCAFC) on Veteran health care utilization and costs. A pre-post cohort design including a nonequivalent control group was used to understand how Veterans’ use of Veteran Affairs health care and total health care costs changed in 6-month intervals up to 3 years after PCAFC enrollment. The control group was an inverse probability of treatment weighted sample of Veterans whose caregivers applied for, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 29 publications
2
72
0
Order By: Relevance
“…As a result, the Department of Veterans Affairs Health Care System (VHA) has developed an extensive program to support family members and caregivers of veterans seriously injured during military service since September 11, 2001 7 ; most of these veterans have a diagnosis of TBI, PTSD, or polytrauma. 8 This supports the idea that while family caregiving is not currently formally acknowledged in the broader US healthcare system, there is much to be learned from the role that family caregivers play in optimizing healthcare outcomes of patients with longterm trauma-related disabilities.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…As a result, the Department of Veterans Affairs Health Care System (VHA) has developed an extensive program to support family members and caregivers of veterans seriously injured during military service since September 11, 2001 7 ; most of these veterans have a diagnosis of TBI, PTSD, or polytrauma. 8 This supports the idea that while family caregiving is not currently formally acknowledged in the broader US healthcare system, there is much to be learned from the role that family caregivers play in optimizing healthcare outcomes of patients with longterm trauma-related disabilities.…”
Section: Introductionmentioning
confidence: 53%
“…No studies examined the effects of financial support for caregivers, a strategy being deployed on a large scale in VHA. 8 Few studies evaluated patient outcomes and no study reported adverse effects. Further, outcome measures varied greatly which contributed to unexplained heterogeneity in some meta-analyses and hampered our efforts to generate evidence on which caregivers and patients are most likely to benefit.…”
Section: Limitations/future Researchmentioning
confidence: 99%
“…The Veterans Affairs Program of Comprehensive Assistance for Family Caregivers (VA‐PCAFC) is illustrative of the complex tradeoffs in structuring programmatic caregiver support. The VA‐PCAFC was initiated in 2011 to assist recovery of post‐9/11 veterans injured during military service by affording a tax‐free monthly stipend to caregivers (from $600 to $2300), training, and mental health services . Early evidence indicates that caregiver participation increased veteran engagement in primary care and mental healthcare and that participants highly valued the supports and services by affording them more confidence in caregiving and skills to help the veteran progress .…”
mentioning
confidence: 99%
“…The VA-PCAFC was initiated in 2011 to assist recovery of post-9/11 veterans injured during military service by affording a tax-free monthly stipend to caregivers (from $600 to $2300), training, and mental health services. 18 Early evidence indicates that caregiver participation increased veteran engagement in primary care and mental healthcare and that participants highly valued the supports and services by affording them more confidence in caregiving and skills to help the veteran progress. 19 Importantly, however, few caregivers knew the full range of services available to them, and those helping over longer periods of time experienced high depressive symptoms and reductions in hours worked for pay.…”
mentioning
confidence: 99%
“…Second, the Department of Veterans Affairs established a national caregiver support program for caregivers of veterans. Besides training and supports such as respite care for all caregivers, more expansive benefits that include a stipend and health insurance are available for qualifying caregivers of veterans from the post-9/11 era who face significant limitations in daily life (Van Houtven et al 2017). Beyond the direct effects on caregiver tasks and intensity, these policies may have unintended consequences to work behavior and future economic security (e.g., foregone Social Security and Medicare benefits) that should be included in the calculation of their net benefits.…”
mentioning
confidence: 99%